Դիցաբանական պատկերացումների արտացոլումը Վանի թագավորության արքայանուններում - Ղարագյոզյան, Ա. Հ. (ՀՀ ԳԱԱ հրատ.)
В странах Древнего Востока обожествление царей было обычным явлением. В составе их имен упоминалось Солнце как символ верховной власти. Свидетельства о культе Солнца наличествуют и в биайнских царских именах. Представители царского рода считались потомками бога Солнца либо его племенем, что в смысловом плане соответствует этническому названию армен.In the countries of Old East, the deification of kings was a usual phenomenon. The Sun was in the origin of their names as a symbol of supreme power. The records of the Sun worship were also reflected in royal names of Biayna. The offspring of the royal dynasty were considered to be the descendants of the God of Sun. The meaning of their names thus corresponded to the name of Armen tribe.
Keywords: Geography; Anthropology; Recreation; Folklore